How to be an engaged intellectual: Case studies and reflections - Jacobs, George (Journal of Modern Languages, 2020)
Engaged intellectuals, for the purposes of this paper, are academics who ask themselves what they can do to maximize the role of their academic and other activities in making the world a better place. This paper recounts and reflects on the experiences of the author and others as they have attempted to put their academic and other skills and understandings to the service of the greater good. These experiences touch on such areas as wildlife conservation, gendered images, the relative role of individuals in social change, Social Interdependence Theory, student centered education, free online publications, Creative Commons, Communities of Practice, organizations of intellectuals, poverty alleviation, plant-based eating, and the Fourth Industrial Revolution. The paper also discusses the author’s own sizeable inadequacies in his attempts to be an engaged intellectuals and the difficulties academics face in changing the world from their place in academia. The author concludes by encouraging intellectuals to make frequent trips outside the familiar comforts of the ivory tower to engage with others in using the many wonders of the modern and natural world to address the many challenges we face.